Continuous production of core-shell protein nanoparticles by antisolvent precipitation using dual-channel microfluidization: Caseinate-coated zein nanoparticles. (February 2017) - Ebert, Sandra; Koo, Charmaine K.W.; Weiss, Jochen; McClements, David Julian
Abstract: Antisolvent precipitation is commonly used to fabricate protein nanoparticles using a simple batch method that involves injecting a protein-solvent mixture into an antisolvent. In this study, the potential of producing core-shell protein nanoparticles by antisolvent precipitation using a continuous dual-channel microfluidization method was investigated. The solvent phase (zein in ethanol) and antisolvent phase (casein in water) were made to impinge on each other at high velocity, which generates intense shear, turbulent, and cavitation forces that ensure thorough mixing and breakup of the phases. Relatively small core-shell protein nanoparticles ( d < 125 nm) could be produced using this method when the conditions were optimized. The mean particle diameter decreased with increasing antisolvent-to-solvent ratio, increasing homogenization pressure, increasing ethanol content in the solvent phase, and decreasing zein content in the solvent phase. Depending on the processing conditions employed, zein particles in the range of about 120 nm to over 1000 nm could be produced. The operating conditions were further optimized to increase the final zein concentration and decrease the organic solvent content while still obtaining small particles. The surface potential of the core-shell protein nanoparticles went from positive at low pH to negative at high pH, with a point of zero charge around pH 5. Electron microscopy indicated that the protein particles formed had a roughly spherical shape. The results suggest that the dual-channel microfluidizer could be used to continuously form protein nanoparticles by antisolvent precipitation. Nevertheless, when the microfluidization method was compared with the simple batch method the size of the particles produced under similar conditions were fairly similar. Graphical abstract: Highlights: Protein nanoparticles were fabricated by dual-channel microfluidization. Zein-in-ethanol and casein-in-water streams were impinged at high velocity. Casein-coated zein nanoparticles were produced by antisolvent precipitation. Nanoparticle size depended on composition and homogenization conditions. Particle sizes were similar by continuous microfluidization & batch methods.